СИНТАКСИЧНА МЕТАФОРА У СВІТЛІ ГРАМАТИКИ КОНСТРУКЦІЙ - Жаботинська, Світлана Анатоліївна (Studia Philologica, 2013)
In this paper, synonymy and semantic variability of syntactic structures is accounted for from the standpoint of Construction Grammar, which views a construction as the unity of a particular schematic form (formal model) and a particular schematic meaning (conceptual model). Synonymy and semantic variability of syntactic structures is caused by the fact that the schematic meaning of a construction, i.e. some basic propositional schema, may be expressed not only with its inherent form, but with the forms of other constructions. The latter case involves interaction of two basic propositional schemas, which is grounded on the syntactic metaphor. Its workings are illustrated with the English syntactic structure NP2 of NP1, the analog of which in Slavic languages is a noun phrase with the Genitive.